G-Quadruplexes in RNA Biology: Recent Advances and Future Directions. Issue 4 (April 2021) - Dumas, Leïla; Herviou, Pauline; Dassi, Erik; Cammas, Anne; Millevoi, Stefania
Abstract : RNA G-quadruplexes (RG4s) are four-stranded structures known to control gene expression mechanisms, from transcription to protein synthesis, and DNA-related processes. Their potential impact on RNA biology allows these structures to shape cellular processes relevant to disease development, making their targeting for therapeutic purposes an attractive option. We review here the current knowledge on RG4s, focusing on the latest breakthroughs supporting the notion of transient structures that fluctuate dynamically in cellulo, their interplay with RNA modifications, their role in cell compartmentalization, and their deregulation impacting the host immune response. We emphasize RG4-binding proteins as determinants of their transient conformation and effectors of their biological functions. Highlights: RG4s are four-stranded structures that have gained growing importance in RNA biology, RNA-associated human diseases, and RNA-based therapeutics. Besides telomere maintenance and gene expression mechanisms, recent advances have highlighted new functions of RG4s in the regulation of RNA expression in mitochondria, in phase separation mechanisms underscoring the formation of membrane-less organelles, and in chemical modifications within transcripts resulting in dynamic shaping of post-transcriptional gene expression pathways. RG4-binding proteins are key players in regulating the dynamic equilibrium of their formation/dissolution in the cell, controlling their biological functions and driving their deregulation associated with human diseases. RG4s may play a role in the strategies that pathogenic organisms or cancer cells use to evade the host's immune responses.